Pengaruh Latihan Push Up Dan Bicep Resistance Band Terhadap Kemampuan Pukulan Depan Atlet Pencak Silat Rayon Psht Maskarabet Kecamatan Alang Alang Lebar - Roy Anugraha; Farizal imansyah; Ilham Arvan Junaidi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research uses a training model given by the trainer in an effort to improve the ability to hit the front blow. This study aims to determine the effect of push up and resistance band training on the front punch ability of PSHT Maskarebet District pencak silat athletes aged 15-17 years. The method in this research is an experiment with a pretest posttest design group design. The population in this study were 20 Rayon Psht Maskarebet Rayon Pencak Silat athletes aged 15-17 years, while the sample was taken equal to the population using a purposive sampling technique. Data were obtained using the front blow test technique. Data were analyzed using the Shapiro-Wilk normality test, homogeneity test and hypothesis testing using the paired sample t-test.The research results obtained that the pretest was the highest score of 39 with an average of 33.00, and the posttest was the highest score of 52 with an average of 47.55. Meanwhile, hypothesis testing used a paired sample T test and based on the calculation results in the table that t count was -26.006 > t table 2.086 and a significant value of 0.000≤0.05, then Ho is rejected. Ha accepted can be concluded based on the results, there is a comparison of the average changes in pretest and posttest from the data that has been obtained, the results of the pretest are an average of 33.00 and the results of the posttest are an average of 47.55, so the difference in the increase in pretest and posttest training is 14.55, that there is a significant influence of push up and bicep resistance band training on the front punch ability of pencak silat athletes from Rayon PSHT Maskarebet, Alang-alanglebar Subdistrict.